A health model based on the clinical practice of manual therapists - Santos, L. (2018)
The evolution of health models occurred along with the changes of the definition of health and rehabilitation but it is still unknown the predominant model of health that fits the clinical practice of physiotherapists who work in manual therapy. Creation of a questionnaire to assess the health model that fits the clinical practice of physiotherapists and after application, verify the knowledge of healthcare models, the degree of agreement between the health model in which physiotherapists based clinical practice and the attitudes and beliefs of physiotherapists in the face of biomedical and biopsychosocial orientation (PABS-PT) and verify the profile and attitudes and behaviors of physiotherapists are related to the health care model. Cross-sectional analytical quantitative study with 203 manual therapists. For the construction of the questionnaire were measured content validity and an accomplished pilot study of reliability. The questionnaire was available for 40 days. Data analysis used the chi-square test, the ordinal correlation coefficient of Spearman and descriptive analysis. Physiotherapists consider that clinical practice is based on the holistic model. This model and the biopsychosocial model is the best-known models, opposite to the ecological model. On the intervention, evaluation directed greater attention to physical symptoms, medical history and causes of the condition, report that work and give more importance to the biological and physical component. After reading the definition of health model, the holistic model stood out. By analyzing the attitudes and beliefs, who referred to the biomedical model as a basis, has increased awareness of the model itself. The choice of model is independent of the profile of physical therapists. Physiotherapists consider their clinical practice is based on the holistic model, however, maintain intervention and evaluation focused on the biomedical model.